2016
DOI: 10.1016/j.matdes.2016.06.097
|View full text |Cite
|
Sign up to set email alerts
|

On the kinetics of thermal oxidation of the thermographic phosphor BaMgAL 10 O 17 :Eu

Abstract: Decreased photoluminescence of the phosphor BaMgAL 10 O 17 :Eu due to oxidation of the europium dopant at high temperatures has been a subject of study for many years in relation to its use in lighting applications. However, understanding of the underlying effects that cause this reduction in photoluminescence remains incomplete and some of the mechanisms proposed in the literature are contradictory. Recent use of this phosphor as a thermal history sensor has extended the range of exposure conditions normally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Exposures of the phosphor in air for 30 mins at 630 • C, and 730 • C, led to a reduction in room temperature brightness of 10% and 57%, respectively [12]. The thermal stability is similar in terms of the temperature/heat treatment duration space to that of BAM:Eu 2+ [17,18]. Note that this is not a concern for short residence times of the particles at high temperatures when used in flows.…”
Section: Introductionmentioning
confidence: 80%
“…Exposures of the phosphor in air for 30 mins at 630 • C, and 730 • C, led to a reduction in room temperature brightness of 10% and 57%, respectively [12]. The thermal stability is similar in terms of the temperature/heat treatment duration space to that of BAM:Eu 2+ [17,18]. Note that this is not a concern for short residence times of the particles at high temperatures when used in flows.…”
Section: Introductionmentioning
confidence: 80%
“…Previously, it was shown that, for BAM : Eu 2+ particles, the temperature calibration remained unchanged before and after combustion in a vessel [9]. This corresponded to an exposure of 0.5 s between 1400 and 2000 K. In a study of much longer exposures (20 min) at 1470 K, only a subtle change in the room temperature emission spectrum was observed [10], translating to an ∼80 K calibration error. Therefore, it is reasonable to assume that short exposure to high temperatures does not alter the luminescence emission spectrum.…”
Section: Introductionmentioning
confidence: 94%
“…However, in Refs [10,11], exposures of several minutes at these temperatures caused the luminescence emission intensity to decrease by orders of magnitude, a phenomenon referred to as thermal degradation. This second phenomenon has not yet been investigated for short exposure times relevant to reactive flows, though it would be problematic since it would compromise the measurement precision.…”
Section: Introductionmentioning
confidence: 99%
“…Among fluorides, oxides, sulfides, and chlorides, which are usually explored as phosphor hosts, oxides are regarded as the most promising candidates because of their excellent physical/chemical durability and mild preparation conditions at ambient pressure. 26,27 It is known that the Eu 2+ :4f 6 5d 1 energy is governed by the nephelauxetic effect and crystal field splitting effect. The former follows the F − < O 2− < Cl − < N 3− < S 2− nephelauxetic sequence.…”
Section: Introductionmentioning
confidence: 99%